(untitled) (Revista Brasileira de Contabilidade e Gestão, 2016)
The study aims to establish the degree of relationship between the ranking of capital market indicators and the ranking of economic-financial indicators of brazilian companies. The design of this research is characterized as a descriptive study, with documentary research procedure, and a quantitative approach. For the study were selected four indicators of capital market and six financial-economic, 27 companies belonging to IBrX-50 listed on the BM&FBovespa, basing the analysis for the periods 2008 to 2012.Were created the rankings of financial-economic and capital markets, through the multicriteria method VIKOR, for each of the years analyzed. We calculated the Kendall correlation between the two rankings, significant positive correlations were observed in the years, 2010, 2011 and 2012. It was concluded that, for some companies the years analyzed, tend to have similarities in positions efficiency in the capital market and the traditional economic-financial indicators, but in other similar positions presented both as distinct.